(untitled) (Al-Academy, 2023)
We can understand interior design as a series of interconnected human principles and goals formed by science and knowledge to build a human product that reveals or gives meaning to things، and this can be presented through ecology as a system concerned with environmental aspects and as part of interior design، seeking to achieve aesthetic and functional values، in an interactive form between spaces The interior and its occupants are within an environmental balance full of life، and the ecological interior design attaches great importance to the embodiment of spiritual aspects in the internal environment، in addition to emphasizing the importance of protecting the environment and preserving resources through saving in its use and using renewable energy.